2012
DOI: 10.1371/journal.pone.0044508
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterisation of Neuroglobin of the Icefish, a Natural Knockout for Hemoglobin and Myoglobin. Comparison with Human Neuroglobin

Abstract: The Antarctic icefish Chaenocephalus aceratus lacks the globins common to most vertebrates, hemoglobin and myoglobin, but has retained neuroglobin in the brain. This conserved globin has been cloned, over-expressed and purified. To highlight similarities and differences, the structural features of the neuroglobin of this colourless-blooded fish were compared with those of the well characterised human neuroglobin as well as with the neuroglobin from the retina of the red blooded, hemoglobin and myoglobin-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 68 publications
(92 reference statements)
3
33
0
Order By: Relevance
“…2A). The spectrum of sulfide-treated neuroglobin under aerobic conditions appears to be a mixture of species and resembles that of O 2 -bound ferrous neuroglobin, which displays absorbance maxima at 413, 543, and 571 nm (34,35). However, accumulation of O 2 -Fe II -Ngb is excluded because similar spectral changes were induced by sulfide under anaerobic conditions with the exception that a slight increase in the intensity at 558 nm was observed, indicating the presence of a small amount of Fe II -Ngb (not shown).…”
Section: Purification and Reaction Of Neuroglobin With Sulfidementioning
confidence: 96%
See 1 more Smart Citation
“…2A). The spectrum of sulfide-treated neuroglobin under aerobic conditions appears to be a mixture of species and resembles that of O 2 -bound ferrous neuroglobin, which displays absorbance maxima at 413, 543, and 571 nm (34,35). However, accumulation of O 2 -Fe II -Ngb is excluded because similar spectral changes were induced by sulfide under anaerobic conditions with the exception that a slight increase in the intensity at 558 nm was observed, indicating the presence of a small amount of Fe II -Ngb (not shown).…”
Section: Purification and Reaction Of Neuroglobin With Sulfidementioning
confidence: 96%
“…We assign this band to the S-S vibration of an iron-bound hydropolysulfide product. This assignment is based on its similarity to the 498 cm Ϫ1 band in a Cys-SS-ligated [2Fe-2S] 2ϩ cluster in the FNR transcriptional factor, which was assigned using 34 S isotope labeling to the S-S stretching mode of the persulfide (57). In the resonance Raman spectrum of Na 2 S 4 , a 482 cm Ϫ1 band was assigned to the S-S vibration (58).…”
Section: Cys-s-sh3 Cys-s-s-s-cysϩh 2 S Reactionmentioning
confidence: 99%
“…To turn this qualitative observation into a quantitative estimate of rate constants for the microscopic processes, we have analyzed the CO rebinding kinetics with the previously proposed kinetic schemes [22,27,28] or suitably modified in order to account for the observed kinetic heterogeneity, paying attention to the differences in bimolecular rebinding, distal His binding and dissociation kinetics (additional information on geminate recombination can be found in the supporting information). Analysis of CO rebinding kinetics to Mb requires the use of a kinetic model detailed in Scheme 2, where the non-exponential geminate recombination is attributed to migration to an internal cavity and is followed by a bimolecular rebinding step [29].…”
Section: Co Rebinding Kinetics To Chmb and Chngb After Laser Flash Phmentioning
confidence: 99%
“…Interestingly, recent theoretical work has shown that for Ngb a relevant escape pathway is located in proximity of the CD region [22] and thus the observed change in k −2 may reflect the modulation introduced by replacing the Mb CD region for the Ngb one. From the microscopic rates it is possible to estimate k on,CO , which for Mb is 0.7 × 10 6 M − 1 s − 1 , a value perfectly in line with the literature [14][15][16].…”
Section: Co Rebinding Kinetics To Chmb and Chngb After Laser Flash Phmentioning
confidence: 99%
See 1 more Smart Citation